SMALL AND MEDIUM INDUSTRY FOR SUSTAINING MADRASA IN GLOBAL CHANGE (Study at Darul Ma’rifat Modern Islamic Boarding School in East Java) - Aswirna, Prima (AT-TA'LIM, 2013)
Any types and size of industry is required for the sustainable development of a Boarding School (Madrasa).  Current study at Darul Ma’rifat Modern Islamic Boarding School in East Java is directed to describe: (1) the size and function of industry at Darul Ma’rifat Modern Islamic Boarding School; (2) the life-skill and the enterprenourships capability of the students; and (3) the effect of life-skills and the enterprenourships capability towards self-fulfilment attitude of students. All of the sixth grade students population (542 pupils) were randomly taken to get 226 students sample by using Slovin  formula : n = N / 1 + N. e2. ( n = sample size, 1 = constanta variable, N = population, e = standard error / 0,05). Data were collected through observation, psychological scale and interview. They were then analyzed using regression supported by Statistical Package of Social Science programme. The results show that: (1) There were thirty unit small and medium industry at Darul Ma’rifat Modern Islamic Boarding School. (2) Life-skills and the enterprenourships capability of the students were taught through practice like; working in bread industry and mini market etc. (3) The mean scored of life-skills and the enterprenourships of the students were 82% categorized high.Copyright © 2013 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v20i3.48